Understanding the Death Benefit Switch Option in Universal Life Policies - Gatzert, Nadine; Hoermann, Gudrun (Journal of Risk and Insurance, 2011)
Universal life policies are the most popular insurance contract design in the United States. They provide either a level death benefit paying a fixed face amount or an increasing death benefit paying a fixed benefit plus the available cash value, and both types include the option to switch from one type to the other. In this article, we investigate the fact that-unlike a switch from level to increasing-a switch from an increasing death benefit to a level death benefit requires neither fees nor evidence of insurability. To assess the impact of the death benefit switch option, we develop a model framework of an increasing universal life insurance policy embedding this option. Consideration of heterogeneity with respect to mortality via a stochastic differential mortality factor enables an investigation of adverse exercise behavior. In a comprehensive simulation analysis, we quantify the net present value of the option from the insurer's perspective using risk-neutral valuation under stochastic interest rates assuming empirical exercise probabilities. Based on our results, we provide policy recommendations for life insurers.
WiSo-Import:2015-03-26:946
Keywords: Increasing death benefit; Death benefit switch option; Heterogeneity in respect of mortality